Vídeo-escultura: A contribuição contemporânea para o tema em Portugal - Moletta, Fernando Flores (CAP - Cadernos de Arte Pública / Public Art Journal, 2022)
The History of Sculpture follows the entire History of Art if we think about its concept as a whole. The history of video in art is relatively recent, it is possible to cite the Dadaist experiences of the 1920s, but it was only after the diffusion of television and the popularization of the portable video camera, from the 1960s, that artists such as Wolf Vostell and Nam June Paik began to incorporate the audiovisual medium into their artistic creations. This paper precisely aims to understand the process of incorporation of video in sculptural matter and vice versa, not only through the historical context in which these operations appear in the History of Art, but also through the study of pioneering artists in this field. In this way, the main interest will be to make a brief overview of the production of contemporary artworks in Portugal that use these means for their realization. In a progressively more virtual world where physical presence is less and less relevant, it is important and necessary to document the works that establish the association between sculptural materiality and the impermanence of the constantly expanding audiovisual field, thus defining a hybrid field in which contemporary art questions which world one actually wants to be in. Such works are here defined by Video-Sculpture.